Identifikasi dan Evaluasi Potensi Geosite pada Kawasan Karst Nagari SImarasok dalam Mendukung Pengembangan Geopark Kabupaten Agam Sumatera Barat - Hary Febrianto; Anggi Angraini; Osronita Osronita; Andri Yanto; Mory Yanti; Fermawati Zega; Desi Eka Putri (Geosfera: Jurnal Penelitian Geografi, 2025)
A geopark is a regional management concept that integrates geological heritage conservation, earth education, and local economic development through community-based geotourism activities. Based on Presidential Regulation No. 9 of 2019 and UNESCO guidelines, a geopark is defined as a protected area containing high-value geosites in terms of geoheritage, geodiversity, biodiversity, and cultural diversity, which is managed sustainably to improve welfare while fostering environmental awareness. In Indonesia, geopark development is directed as a conservation strategy and regional development instrument, including in West Sumatra Province, which includes a geopark program in its tourism development master plan. In this context, the active role of local governments and communities is key to the successful management of geoparks as geotourism destinations with educational, ecological, and economic value.